2017
DOI: 10.33225/jbse/17.16.123
|View full text |Cite
|
Sign up to set email alerts
|

Improving High-School Students’ Conceptual Understanding and Functionalization of Knowledge About Digestion Through the Application of the Interdisciplinary Teaching Approach

Abstract: Adolescents are considered as a nutritionally vulnerable subgroup because of their alimentary behaviours. Considering that alimentary habits are strongly influenced by knowledge about digestion, an experiment was conducted with aim to determine whether conceptual understanding and functionalization of this knowledge can be improved by the interdisciplinary teaching approach. The experiment encompassed 258 students attending the fourth year of high school. No statistically significant difference in the level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…Interdisciplinary learning integrates two or more disciplines into coherent connections, enabling students to establish relevant connections and generate meaningful associations (You, 2017). The current research results suggested that the interdisciplinary teaching approach has a positive effect on students' academic achievement, motivation, attitudes toward the course, problem-solving, critical thinking, gaining new perspectives, and lifelong learning skills (Cecchini & Carriedo, 2020; Cordogon & Stanciak, 2000; Howlett et al, 2016; Jones, 2009; Kander, 2003; Putica & Trivić, 2017; Walshe, 2017; White & Carpenter, 2008; Yang, 2009).…”
Section: Introductionmentioning
confidence: 76%
“…Interdisciplinary learning integrates two or more disciplines into coherent connections, enabling students to establish relevant connections and generate meaningful associations (You, 2017). The current research results suggested that the interdisciplinary teaching approach has a positive effect on students' academic achievement, motivation, attitudes toward the course, problem-solving, critical thinking, gaining new perspectives, and lifelong learning skills (Cecchini & Carriedo, 2020; Cordogon & Stanciak, 2000; Howlett et al, 2016; Jones, 2009; Kander, 2003; Putica & Trivić, 2017; Walshe, 2017; White & Carpenter, 2008; Yang, 2009).…”
Section: Introductionmentioning
confidence: 76%
“…However, most of these related to pre‐service teachers. Only one included study was relevant for the current overview (Putica & Trivic, 2017 as cited in Winarno et al., 2020). It reported quasi‐experimental research with 258 high school students, which aimed to determine whether conceptual understanding of digestion can be improved by an interdisciplinary teaching approach.…”
Section: Resultsmentioning
confidence: 99%
“…Kontekstualno učenje pomaže u sagledavanju odnosa između nauke i svakodnevnog života. Primena kontekstualnog pristupa u nastavi prirodnih nauka doprinosi boljem konceptualnom razumevanju gradiva prirodnih nauka, kao i razvoju pozitivnijeg odnosa prema prirodnim naukama, naročito kod učenika sa posebnim potrebama (Putica & Trivić, 2017). Pored toga, predstavljanje gradiva u kontekstima koji su učenicima bliski i koje učenici poznaju predstavlja dobru osnovu za razvijanje unutrašnje motivacije učenika (Schwartz-Bloom et al, 2011).…”
Section: Rezultati Učenje U Neformalnim Obrazovnim Kontekstimaunclassified